(3GdfXGe GdJGOjHi ddehXa GdYGe ai bWQ OQGSI ebGQfI (B/ s - (3MUI GMeO YHOGddg GdSdjWis; (3LGHQ LGO fUGQs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2007)
(3JfbSe gPI GdOQGSI Gdi aUhd GQHYI fJMOK ai GdaUd GdGhd Yf JMOjO acQI GdeNGdaI GdJGOjHjI h HjGf GQcGfgG h ai GdaUd GdKGfi Yf GdSdWI GdeNJUI HGdJGOjH ai bWQ hai GdaUd GdKGdK Yf GdLRGAGJ GdJGOjHjI GeG ai GdaUd GdQGHY h GdGNjQ afJfGhd ajI GdVeGfGJ GdJGOjHjI ddehXa GdYGe ai bWQ h ai cd aUd ef gPI GdaUhd GdGQHYI SfYbO GdebGQfI Hjf GdhVY ai GdfXGe GdbGfhfi GdbWQis
(3jTJed Ydi edGMbs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2007s
(3HHdjhLQGajG(B: (3UaMGJ (B203-206s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdYGes; (3GdeNGdaI GdJCOjHjIs; (3GdehXa GdYGes; (3bWQs; (3GdLRGA GdJCOjHjs; (3GdbGfhf GdbWQjs; (3GdLRGA Gdegfjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes